Role And Correlation Of Synthesis, Size And Morphology To The Magnetic Properties Of Cobalt And Cobalt/Gold Bimetallic Hierarchical Nanostructures - Khe, Cheng Seong (2013)
Cobalt is a ferromagnetic material while cobalt-gold bimetallic particles are expected to have modulated magnetic properties. Besides, gold nanostructure is also a good plasmonic material. However, cobalt is susceptible to oxidation in aqueous environment. The oxidised layer can harm the magnetic properties. Therefore, in order to avoid oxidation of cobalt, this work was devoted to the synthesis of cobalt and cobalt-gold bimetallic hierarchical particles using polyol method cum galvanic replacement reaction. A number of synthesis conditions were experimented in order to investigate their impacts on the morphologies of the cobalt particles produced. The parameters studied including reaction time, sodium hydroxide, concentration of cobalt salt, reaction temperature, reducing agent and surfactants. Various morphologies were successfully prepared such as hierarchical microspheres, hierarchical polyhedral shape, hierarchical raspberry like, truncated hexagonal bipyramid, flower-like, elongated and quasi cubic-like particles. All of these hierarchical cobalt particles exhibited their own unique magnetic properties. Sample prepared from 1mmol cobalt chloride, 2 mmol of sodium hydroxide, 5 mmol of hydrazine hydrate and 3.0% (w/v) of sodium dodecyl sulfate has a mixture of quasi cubic and elongated particles. It has the highest coercivity of about 290 Oe. Cobaltgold bimetallic hierarchical particles were prepared by galvanic replacement reaction where cobalt acted as sacrificial template. Bimetallic particles with hollow hierarchical structure and arbitrary shapes were produced under different synthesis conditions.